Pengembangan LKPD Berbasis Role Playing Pada Pembelajaran IPAS Dalam Kurikulum Merdeka Dengan Materi Indonesiaku Kaya Budaya Untuk Meningkatkan Hasil Belajar Siswa Kelas IV Sekolah Dasar - Nurul Sahpitri Tanjung; Sri Ramadhina; Syahrial Syahrial (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This research aims to improve thematic LKPD learning using a role-playing model in grade 5 elementary schools in Bengkulu City.This research is research and development (R&D) carried out by modifying Thiagarajan and Sammel's four-dimensional model.This research shows that LKPD in thematic learning using the role-playing model received a score of 78.10 in the "good" category at level 1 by LKPD experts and 89.25 in the "very good" category at level 2 by 90 students. He gave me the answer which is very good.Therefore, from the research that has been conducted it can be concluded that LKPD using the social and natural sciences (IPAS) role-playing learning model in the independent curriculum for grade IV elementary school can be classified as a very good LKPD and can be used for learning.